(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Changes occurring in the economic, social, political, scientific, and cultural spheres of society influence the development of language. For instance, in the process of globalization, numerous new words, terms, and concepts are entering our language, leading to its enrichment based on these new concepts. In turn, this phenomenon demonstrates the significant role of sociolinguistic factors in language development. The causes of changes in the national language are linked to various factors, such as political, social, cultural, and technological conditions, and these factors are complex in nature. The article explores the historical development, current state, and the place and role of the community in the evolution of the national language.